Midpalatal Suture Ossification and Skeletal Maturation: A Comparative Computerized Tomographic Scan and Roentgenographic Study - Manish Thadani; Usha Shenoy; Bhaskar Patle; Anshu Kalra; Shirish Goel; N Toshinawal (Wolters Kluwer Medknow Publications, 2010)
The main aim of this study was to evaluate and compare the ossification of the midpalatal suture using cross-sectional maxillary occlusal radiograph and computerized tomographic scan of the hard palate in the axial direction. The percentage of the ossification thus obtained was correlated with the skeletal maturation indicators like (CVMI categories and MP3 stages) in Group I subjects (8.0-16.0 years) and with chronological age in group II subjects (16.1-25.0 years). The radiograph of the middle phalanx of the third finger and lateral cephalogram in occlusion were taken for the Group I subjects. The total sample size of the study comprised of 21 subjects with transverse maxillary deficiency. The percentage of the ossification of the midpalatal suture was calculated using suture obliteration index described by Persson and Thilander. The results of the study revealed that the total amount of ossification of the MPS in Group I subjects with computerized tomographic scan (22.56 ΁ 3-62%) was significantly less compared to cross-sectional maxillary occlusal radiograph (5822 ΁ 3.79) at the end of skeletal maturation (p < 0-001). There was sudden spurt in the ossification of the MPS after CVMI category 4/MP3 H stage. In Group II subjects CT scan again showed significantly less amount of the ossification (40.78 ΁ 19,73) compared to maxillary occlusal radiograph (60.32 ΁ 14,41) in the total length of the MPS (p < 0.05). Thus CT scan of the hard palate showed less than 50% of the midpalatal suture ossification at the age of 25 years approximately. This was due to advantages of the computed tomographic technology. i.e. no superimposition of the overlying and adjacent structure, exact localization and accurate assessment of the MPS ossification over the conventional radiography.